2018
DOI: 10.1038/s41598-018-34591-5
|View full text |Cite
|
Sign up to set email alerts
|

Brassica yellows virus’ movement protein upregulates anthocyanin accumulation, leading to the development of purple leaf symptoms on Arabidopsis thaliana

Abstract: Poleroviruses are widely distributed and often of great economic importance because they cause a variety of symptoms, such as the rolling of young leaves, leaf color changes, and plant decline, in infected plants. However, the molecular mechanism behind these viral-induced symptoms is still unknown. Here, we verified the pathogenicity of the polerovirus Brassica yellows virus (BrYV) by transforming its full-length amplicon into Arabidopsis thaliana, which resulted in many abnormal phenotypes. To better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 85 publications
(85 reference statements)
2
19
0
Order By: Relevance
“…Ustilago maydis triggered anthocyanin induction in maize 80 , and anthocyanin-enriched tomato fruits exhibited lower susceptibility to gray mold 81 . Moreover, antibacterial, antifungal and antiviral activities of certain anthocyanins were also reported [82][83][84] .…”
Section: Discussionmentioning
confidence: 95%
“…Ustilago maydis triggered anthocyanin induction in maize 80 , and anthocyanin-enriched tomato fruits exhibited lower susceptibility to gray mold 81 . Moreover, antibacterial, antifungal and antiviral activities of certain anthocyanins were also reported [82][83][84] .…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it is important to study how MP participates in the movement of the virus in hosts. MP plays an essential role in virus infection, which not only promotes the intercellular movement and systemic movement of the virus but also serves as a critical pathogenic factor to cause purple symptoms in the infected leaves [44]. Thus, we establish a specific detection system by developed antisera against three different MPs, which is indispensable to study the occurrence and distribution of viruses and the function of MP.…”
Section: Discussionmentioning
confidence: 99%
“…There are two BrYV inocula were selected for aphids feeding and transmission. Firstly, the seedlings of the seventh generation transgenic A. thaliana line 412 with BrYV full-length cDNA clone grown to 3-4 weeks with all shown typical purple symptoms and were confirmed to carry BrYV by western blotting and RT-PCR which were used as fresh BrYV inocula [14]. And the transgenic plants were also kept at -20 ℃ as frozen BrYV inocula.…”
Section: Virus Inocula Were Ready For Transmissionmentioning
confidence: 99%
“…genotypes (BrYV-A, B, and C) according to sequence analysis, the full-length infectious cDNA clones of these three genotypes have been developed successfully [8,[10][11][12][13]. Previously work have shown that the full-length amplicon of the virus has been successfully transferred into Arabidopsis thaliana and obtained stable genetically transgenic lines named 111 and 412 which all exhibited severe symptoms including dwarfing and the purple leaves [14]. BrYV P0 protein interacted with the plant SKP1 contributes to its stability thereby evading autophagy and proteasomal degradation [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation